A resin material and its preparation method and application

By using high hardness and high wear resistance resin materials composed of the upper and lower layer parts, the problems of insufficient wear resistance, impact resistance and bonding strength of existing denture materials are solved, and the service life and impact resistance of resin teeth are significantly improved.

CN119770724APending Publication Date: 2025-04-08AIDITE (QINHUANGDAO) TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411983783.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The wear resistance, impact resistance and bond strength between the denture and the foundation of the existing denture materials lead to short service life and easy breakage.

Method used

A resin material consisting of the upper and lower parts is used. The hardness of the upper part is 30-90HV1, the maximum stress strength factor of the lower part is ≥1.9MPa·m1/2, the total breaking work is ≥900J/m2, and the binding strength is ≥15MPa, and is prepared by a hot pressing process.

Benefits of technology

It significantly improves the service life of resin teeth, enhances impact resistance and wear resistance, and improves the bonding between the denture and the foundation, avoiding breakage and shedding problems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005223524670000071
    Figure BDA0005223524670000071
  • Figure BDA0005223524670000072
    Figure BDA0005223524670000072
  • Figure BDA0005223524670000081
    Figure BDA0005223524670000081
Patent Text Reader

Abstract

The present invention relates to the technical field of dental materials, and in particular to a resin material and a preparation method and application thereof. The resin material provided by the present invention is composed of an upper layer and a lower layer; the hardness of the upper layer is 30 to 90 HV1; the maximum stress intensity factor of the lower layer is ≥1.9 MPa·m 1 / 2 , total fracture work ≥900J / m 2 The bonding strength between the upper layer and the lower layer is ≥15MPa. The upper layer (cut end) of the resin material provided by the present invention has high hardness and high wear resistance, and is not easy to wear. The lower layer has good toughness, excellent impact resistance, and is not easy to break. At the same time, the bonding strength between the upper and lower layers is high, and the use of the upper and lower layers to prepare resin teeth can significantly improve the service life of the resin teeth.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of dental materials, and in particular to a resin material and a preparation method and application thereof. Background Art

[0002] Tooth loss has physiological and psychological effects on patients. Patients hope to get a beautiful and durable restoration to replace the missing teeth to restore normal chewing function. Resin teeth are widely used in clinical full dentures and partial removable dentures due to their good operating performance and color and texture similar to natural teeth. The main material for making removable dentures is polymethyl methacrylate (PMMA), which has the disadvantages of unsatisfactory surface hardness and low wear resistance, resulting in a relatively low service life of synthetic resin teeth.

[0003] In addition, there is another problem when polymethyl methacrylate resin is used to make denture bases, that is, its mechanical properties, especially its impact resistance, are poor. Since the motor function of older prosthesis wearers is usually limited, the prosthesis may occasionally fall onto hard surfaces (ceramic tiles, wash basins) during cleaning, which may cause fragmentation or breakage. Therefore, it is urgent to prepare denture bases with high impact resistance to solve the problem of easy breakage of existing base materials and improve the service life of the whole mouth.

[0004] Furthermore, the bonding strength between the denture and the base in the prior art needs to be improved. Insufficient bonding strength may cause the denture to break or fall off during use.

[0005] Currently, there is no resin material that has both high wear resistance, high impact resistance and good bonding strength between the denture and the base. Summary of the invention

[0006] In view of this, the purpose of the present invention is to provide a resin material and its preparation method and application. The resin material has high hardness and high wear resistance, excellent impact resistance, and is not easy to break. At the same time, the upper and lower layers have good bonding strength. It is used to prepare resin teeth, which can significantly improve the service life of the resin teeth.

[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0008] The present invention provides a resin material, which consists of an upper layer and a lower layer; the hardness of the upper layer is 30 to 90 HV1; the maximum stress intensity factor of the lower layer is ≥1.9 MPa·m 1 / 2 , total fracture work ≥900J / m 2 ; The bonding strength between the upper layer and the lower layer is ≥15MPa.

[0009] Preferably, the color of the upper layer is tooth color; and the color of the lower layer is gum color.

[0010] Preferably, the raw materials for preparing the upper layer include, by weight percentage: 30-85% of a first organic resin, 0.1-3% of a first initiator, 14.8-69.8% of an inorganic filler, and 0.01-1% of a first colorant;

[0011] The raw materials for preparing the lower layer include, by weight percentage: 80-97% of a second organic resin, 0.1-3% of a second initiator, 0.01-19.8% of a core-shell toughening agent, and 0.01-1% of a second colorant;

[0012] The first organic resin and the second organic resin are of the same type;

[0013] The core-shell toughening agent has a two-phase structure of a rubber phase and a plastic phase.

[0014] Preferably, the core-shell toughening agent comprises methyl methacrylate-butadiene-styrene copolymer.

[0015] Preferably, the first organic resin and the second organic resin include polymers and / or monomers; the polymer includes one or more of polymethacrylate, bisphenol A dimethacrylate, urethane dimethacrylate, polycyclohexyl methacrylate, polyvinyl chloride, polystyrene, polyoxymethylene, polyacetaldehyde and polyurethane;

[0016] The monomer includes one or more of methacrylate, 2-phenoxyethyl methacrylate, ethylene glycol dimethacrylate, 1,6-hexanediol diacrylate, and dimethacrylate urethane.

[0017] Preferably, the inorganic filler includes one or more of glass, glass ceramics, calcium salts, metal oxides, aluminum silicate, silicon carbide, strontium fluoride, kaolin, clay, mica, aluminum sulfate, barium sulfate, calcium hydroxide, strontium hydroxide, zeolite, silicon dioxide, hydroxyapatite and ytterbium trifluoride.

[0018] Preferably, the glass comprises one or more of fluorine glass, borosilicate glass, soda glass, barium glass, glass containing strontium or zirconium, barium aluminosilicate glass and fluoroaluminosilicate glass;

[0019] The metal oxide includes one or more of aluminum oxide, zirconium oxide, barium oxide and zinc oxide;

[0020] The calcium salt includes one or more of calcium phosphate, calcium fluoride, calcium carbonate and calcium sulfate.

[0021] Preferably, the first colorant includes one or more of vanadium yellow, cerium praseodymium yellow, lemon yellow, iron oxide yellow, chrome yellow, sunset red, iron oxide red, erbium oxide, chromium oxide, iron oxide brown, iron oxide black, carbon black, titanium dioxide and organic pigments.

[0022] Preferably, the second colorant includes one or more of vanadium yellow, cerium praseodymium yellow, lemon yellow, iron oxide yellow, chrome yellow, sunset red, iron oxide red, erbium oxide, chromium oxide, iron oxide brown, iron oxide black, carbon black, titanium dioxide, organic pigment red and imitation bloodshot.

[0023] The present invention provides a method for preparing the resin material described in the above scheme, comprising the following steps:

[0024] Mix the raw materials in the upper layer to obtain an upper layer material;

[0025] Mixing the raw materials of the lower layer to obtain the lower layer material;

[0026] The upper layer material and the lower layer material are stacked and then hot pressed to obtain the resin material.

[0027] Preferably, the hot pressing time is ≥15 min, the temperature is ≥100° C., and the pressure is ≤25 MPa.

[0028] The present invention provides the use of the resin material described in the above scheme or the resin material prepared by the preparation method described in the above scheme in preparing dentures.

[0029] The present invention provides a resin material, which consists of an upper layer and a lower layer; the hardness of the upper layer is 30 to 90 HV1; the maximum stress intensity factor of the lower layer is ≥1.9 MPa·m 1 / 2 , total fracture work ≥900J / m 2 The bonding strength between the upper layer and the lower layer is ≥15MPa. The upper layer (cut end) of the resin material provided by the present invention has high hardness and high wear resistance, and is not easy to wear. The lower layer has good toughness, excellent impact resistance, and is not easy to break. At the same time, the bonding strength between the upper and lower layers is high, and the use of the upper and lower layers to prepare resin teeth can significantly improve the service life of the resin teeth. DETAILED DESCRIPTION

[0030] The present invention provides a resin material, which consists of an upper layer and a lower layer; the hardness of the upper layer is 30 to 90 HV1; the maximum stress intensity factor of the lower layer is ≥1.9 MPa·m 1 / 2 , total fracture work ≥900J / m 2 ; The bonding strength between the upper layer and the lower layer is ≥15MPa.

[0031] In a specific embodiment, the hardness of the upper layer can be 30, 40, 50, 60, 70, 80 or 90 HV1; the maximum stress intensity factor of the lower layer is preferably 1.9 to 2.7 MPa·m 1 / 2 , specifically 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6 or 2.7 MPa·m 1 / 2 The total fracture work of the lower layer is preferably ≥ 1500 J / m 2 , more preferably ≥2500 J / m 2 In a specific embodiment, the total work of fracture of the lower layer can be 1223, 1438, 1856, 2433, 2700 or 3000 J / m 2 ; The present invention has no special requirements for the upper limit of the total work of fracture. In the present invention, the bonding strength between the upper layer and the lower layer is preferably ≥20MPa, more preferably ≥24MPa, and in a specific embodiment, it can be 24, 26, 28 or 30MPa. The present invention has no special requirements for the upper limit of the bonding strength.

[0032] In the present invention, the color of the upper layer is preferably tooth color; the color of the lower layer is preferably gum color. In the present invention, the thickness of the upper layer is preferably 30-50% of the total thickness of the resin material. In a specific embodiment, the thickness of the upper layer can account for 30%, 40% or 50% of the total thickness of the resin material.

[0033] Calculated by mass percentage, the raw materials for preparing the upper layer include: 30-85% of a first organic resin, 0.1-3% of a first initiator, 14.8-69.8% of an inorganic filler and 0.01-1% of a first colorant.

[0034] Unless otherwise specified, the materials and equipment used in the present invention are all commercially available products in the art.

[0035] In a specific embodiment, the content of the first organic resin can be 30%, 40%, 50%, 60%, 70%, 80% or 85%; the content of the first initiator can be 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5% or 3%; the content of the inorganic filler can be 14.8%, 20%, 25%, 30%, 40%, 45%, 50%, 55%, 60%, 65% or 69.8%; the content of the first colorant can be 0.01%, 0.03%, 0.05%, 0.07 or 1%.

[0036] The present invention can improve the wear resistance of the upper layer by controlling the content of the inorganic filler within the above range, and can also prevent the excessive content of the inorganic filler from affecting the polymerization effect of the resin during the hot pressing process.

[0037] In the present invention, the first organic resin preferably includes a polymer and / or a monomer; when the first organic resin includes both a polymer and a monomer, the mass of the polymer is preferably greater than the mass of the monomer.

[0038] In the present invention, the polymer preferably includes one or more of polymethacrylate, bisphenol a dimethacrylate (BPA-DMA), urethane dimethacrylate (UDMA), polycyclohexyl methacrylate, polyvinyl chloride (PVC), polystyrene (PS), polyoxymethylene (POM), polyacetaldehyde and polyurethane (PU); the polymethacrylate preferably includes one or more of polymethyl methacrylate (PMMA), polyethyl methacrylate (PEMA), polypropyl methacrylate (PPMA), polybutyl methacrylate (PBMA) and polyhexyl methacrylate (PHMA).

[0039] In the present invention, the monomer preferably includes one or more of methacrylate, 2-phenoxyethyl methacrylate, ethylene glycol dimethacrylate (EGDMA), 1,6-hexanediol diacrylate (HDDA) and dimethacrylate urethane (UDMA); the methacrylate preferably includes one or more of methyl methacrylate (MMA), ethyl methacrylate (EMA), propyl methacrylate (PMA) and butyl methacrylate (BMA).

[0040] The present invention has no special requirements on the type of the first initiator, and an initiator well known in the art can be used, such as one or more of benzoyl peroxide, tert-butyl peracetate, diisopropylbenzene peroxide, tert-butyl peroxy-2-ethylhexanoate and tert-butyl perbenzoate.

[0041] In the present invention, the inorganic filler preferably includes one or more of glass, glass ceramics, calcium salts, metal oxides, aluminum silicate, silicon carbide, strontium fluoride, kaolin, clay, mica, aluminum sulfate, barium sulfate, calcium hydroxide, strontium hydroxide, zeolite, silicon dioxide, hydroxyapatite and ytterbium trifluoride; the glass preferably includes one or more of fluorine glass, borosilicate glass, sodium glass, barium glass, glass containing strontium or zirconium, barium aluminum silicate glass and fluoroaluminosilicate glass; the metal oxide preferably includes one or more of aluminum oxide, zirconium oxide, barium oxide and zinc oxide; the calcium salt preferably includes one or more of calcium phosphate, calcium fluoride, calcium carbonate and calcium sulfate. In the present invention, the size of the inorganic filler is preferably nanometer-scale.

[0042] In the present invention, the inorganic filler has the following functions: (1) The filler itself has a relatively high hardness. When the denture contacts and rubs against food or other objects in the oral environment, these hard particles can withstand the force of friction. (2) The inorganic filler can enhance the rigidity and strength of the denture material. When the filler is evenly dispersed in the denture material, it can play a role in strengthening the skeleton. (3) The bonding and stress transfer between the inorganic filler and the resin matrix: When the filler and the resin matrix are tightly bonded by chemical bonding or physical adsorption, the stress generated during the friction process can be effectively transferred between the filler and the matrix. (4) The filler can improve the surface properties of the denture material, such as reducing the friction coefficient, filling gaps, etc.

[0043] In the present invention, the first colorant preferably includes one or more of vanadium yellow, cerium praseodymium yellow, lemon yellow, iron oxide yellow, chrome yellow, sunset red, iron oxide red, erbium oxide, chromium oxide, iron oxide brown, iron oxide black, carbon black, titanium dioxide and organic pigments.

[0044] In terms of mass percentage, the raw materials for preparing the lower layer include: 80-97% of a second organic resin, 0.1-3% of a second initiator, 0.01-19.8% of a core-shell toughening agent and 0.01-1% of a second colorant.

[0045] In a specific embodiment, the content of the second organic resin can be 80%, 83%, 85%, 87%, 90%, 95% or 97%; the content of the second initiator can be 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5% or 3%; the content of the core-shell toughening agent can be 0.01%, 0.1%, 1%, 3%, 5%, 8%, 10%, 12%, 15%, 17% or 19.8%; the content of the second colorant can be 0.01%, 0.03%, 0.05%, 0.08% or 1%.

[0046] The present invention can achieve a good toughening effect by controlling the content of the core-shell toughening agent within the above range, thereby achieving the effect of improving the impact resistance of the lower layer.

[0047] In the present invention, the type of the second organic resin is preferably the same as the type of the first organic resin. When the upper part and the lower part use the same organic resin, on the one hand, during the polymerization reaction under hot pressing, the monomer molecules will be connected to each other through chemical bonds to form a polymer, and at the interface between the two, the molecular chains can continue with each other, thereby generating a strong chemical binding force. On the other hand, the materials after the polymerization of the same monomers have similar molecular chains in morphology and physical properties. When the base and the denture are combined, due to the similarity of the molecular chains, the molecular chains can be better close to each other and attract each other at the bonding interface, and the intermolecular forces (such as van der Waals forces) can also play a better role. This physical intermolecular force works together with the chemical binding force to make the bond between the base and the denture part stronger and increase the bonding force.

[0048] In the present invention, the core-shell toughening agent has a two-phase structure of a rubber phase and a plastic phase; the core-shell toughening agent preferably includes methyl methacrylate-butadiene-styrene copolymer (MBS).

[0049] The present invention adds a core-shell toughening agent to the lower layer so that the lower layer has high fracture toughness. When the core-shell toughening agent is MBS, the specific mechanism of action is as follows: ① Microscopic mechanism: MBS is a thermoplastic elastomer, which has a two-phase structure of a rubber phase and a plastic phase. In the lower layer (denture base) material, the rubber phase of MBS can absorb and disperse the impact energy, while the plastic phase of MBS provides the strength and rigidity of the material to maintain the shape of the denture base. ② Synergistic effect: MBS has good compatibility with the second organic resin in the denture base, and it can be evenly dispersed in the base material system. This uniform dispersion enables MBS to form an effective impact-resistant network in the entire denture base. When an impact occurs, stress can be quickly transmitted and dispersed through this network, thereby avoiding local stress concentration and causing the denture base to rupture. ③ Interface effect: The interface between MBS and other components of the denture base also helps to improve the impact resistance. At the interface, MBS can interact with other components by chemical bonding or physical adsorption, and this interface interaction can prevent the expansion of cracks.

[0050] In the present invention, the second colorant preferably includes one or more of vanadium yellow, cerium praseodymium yellow, lemon yellow, iron oxide yellow, chrome yellow, sunset red, iron oxide red, erbium oxide, chromium oxide, iron oxide brown, iron oxide black, carbon black, titanium dioxide, organic pigment red and imitation bloodshot.

[0051] The present invention provides a method for preparing the resin material described in the above scheme, comprising the following steps:

[0052] Mix the raw materials in the upper layer to obtain an upper layer material;

[0053] Mixing the raw materials of the lower layer to obtain the lower layer material;

[0054] The upper layer material and the lower layer material are stacked and then hot pressed to obtain the resin material.

[0055] In the present invention, the time of the hot pressing is preferably ≥15 min, more preferably 15 to 100 min, and in a specific embodiment, it can be 15 min, 25 min, 30 min, 40 min, 50 min, 65 min, 75 min, 85 min or 100 min; the temperature of the hot pressing is preferably ≥100°C, more preferably 100 to 180°C, and in a specific embodiment, it can be 100°C, 130°C, 140°C, 150°C, 160°C or 180°C; the pressure of the hot pressing is preferably ≤20 MPa, more preferably 5 to 20 MPa, and in a specific embodiment, it can be 5, 10, 15 or 20 MPa.

[0056] In the present invention, the first organic resin and the second organic resin are polymerized and cross-linked during the heat pressing process.

[0057] The present invention provides the use of the resin material described in the above scheme or the resin material prepared by the preparation method described in the above scheme in preparing dentures.

[0058] The resin material provided by the present invention and its preparation method and application are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0059] In the following embodiments and comparative examples, the inorganic fillers are all nano-scale fillers, and the thickness ratio of the tooth part to the base part is 4:6.

[0060] Examples 1 to 6

[0061] The resin materials of Examples 1 to 6 are composed of the components shown in Table 1 and Table 2 according to weight percentage, and the preparation method is as follows:

[0062] The raw materials for preparing the tooth part are mixed evenly according to proportion, and then flattened to obtain an upper layer material;

[0063] The raw materials for the base part are mixed evenly according to proportion, and then flattened to obtain the lower layer material;

[0064] The lower layer material and the upper layer material are sequentially placed in a mold for hot pressing. The hot pressing parameters are shown in the table. After cooling, the mold is taken out to obtain a resin material.

[0065] Table 1 Raw material composition of resin materials in Examples 1 to 3

[0066]

[0067] Table 2 Raw material composition of resin materials in Examples 4 to 6

[0068]

[0069]

[0070] Comparative Examples 1 to 7

[0071] The resin materials of Comparative Examples 1 to 7 are composed of the components shown in Tables 3 to 4 in terms of weight percentage. The preparation method is the same as that of the embodiment, and the pressing parameters are shown in Tables 3 to 4.

[0072] Table 3 Raw material composition of resin materials in comparative examples 1 to 3

[0073]

[0074]

[0075] Table 4 Raw material composition of resin materials of comparative examples 4 to 7

[0076]

[0077]

[0078] Performance Test:

[0079] 1. Hardness test:

[0080] Sample preparation: Use a cutting machine to cut a sample with the size of length × width × height = (20±1) mm × (20±1) mm × (10±1) mm. Use 2000-grit sandpaper to wet-polish the test surface of the sample until it is smooth, flat and pollution-free. Use a 2B pencil to lightly paint the test points.

[0081] Testing steps: Use a Vickers hardness tester, set the applied force to 1kgf, set the holding time to 10s, select different positions for testing 3 times according to the above method, and take the average value. If the single value is ≥18HV1, the material meets the requirements.

[0082] 2. Maximum stress intensity factor and total fracture work test:

[0083] Use a cutting machine to cut 10 specimens with the dimensions of length × width × height = 39mm × (8.0 ± 0.2) mm × (4.0 ± 0.2) mm along the middle of the specimen, use 2000-grit sandpaper to polish the specimen, measure the specimen dimensions, and be accurate to 0.01mm; the deviation of the three-point height measurement along the long axis of the specimen should not exceed ±0.02mm. The specimen should be flat and uniform in height. Use an electric saw to process a notch with a depth of (3.0 ± 0.2) mm in the middle of the specimen, and use a microscope to test the length of the prefabricated notch and record it.

[0084] Test steps: Place 10 test strips that meet the requirements in a container filled with water at (37±1)℃ for 7d±2h. Before the test, store the test strips in another container filled with water at (23±1)℃ for (60±15)min. After the above conditions, take out a test strip from the water and wipe it dry with a clean towel. Place the test strip on the support frame of the bending test device with a span of 32mm. The fine tip of the test strip is facing away from the load punch. Make sure the fine tip is in the center of the support frame. The load punch of the universal testing machine gradually increases the force from zero at a constant displacement of (1.0±0.2)mm / min until the maximum pressure is passed and the notch almost reaches the opposite side of the test strip. When the load is reduced to 1% of the maximum load, the test is considered to be over, and the maximum stress and area are recorded.

[0085] The maximum stress intensity factor is calculated according to formula 1:

[0086]

[0087] In formula 1:

[0088] K max ——maximum stress intensity factor;

[0089] P max - the maximum load applied to the test specimen;

[0090] b——the width of the specimen, in millimeters (mm);

[0091] h——thickness of the specimen, in millimeters (mm);

[0092] l——support span, in millimeters (mm);

[0093] a——notch length.

[0094] Calculation of total fracture work:

[0095] Calculate the area under the load / deflection curve according to the formula U = ∫Fd△ (since the curve can be approximated as a triangle, calculate directly according to the triangle area formula of the curve); calculate the total fracture work according to the formula W = U / [2b(ha)]×1000J / m 2 .

[0096] 3. Ultimate flexural strength and flexural elastic modulus test:

[0097] Sample preparation: Store five test strips with a length of (64±1) mm, a width of (10.0±0.2) mm, and a height of (3.3±0.2) mm in water at (37±1)°C for (50±2) h.

[0098] Testing steps: Use a universal testing machine (AGS-X-20KND) for testing, select the test scheme "Hot Coagulation-Ultimate Flexural Strength", speed: (5±1) mm / min, span: (50±0.1) mm, test surface: (10±0.2)×(64±0.2) mm; enter the corresponding test parameters, take the test strip out of the water bath and immediately place it symmetrically on the test platform of the electric tensile testing machine immersed in a (37±1)℃ water bath, click to start the test, until the specimen breaks, the test is completed, and the test report is output.

[0099] 4. Bonding strength

[0100] Use a cutting machine to cut 5 samples with an upper diameter of 5 mm, a height of 2.5 mm, and a lower diameter of 12 mm, and a height of 8 mm (the upper part is tooth-colored, and the lower part is base-colored). Alternately immerse the samples in water at (5±1)°C for 30s to 35s and in water at (55±1)°C for 30s to 35s, and repeat 5000 times.

[0101] Testing steps:

[0102] Before testing, remove the sample from the water, measure the two diameters of the crown and bridge resin sample at right angles to each other, wipe the sample dry, and make sure that the surface of the metal plate is in contact with the fixed plate of the device. Then put the device into the universal tensile testing machine, and apply force to the sample at a constant crosshead speed of 0.75mm / min or a loading rate of (50±16)N / min until it breaks, and record the force value F when the sample breaks.

[0103] The test results are summarized in Table 5.

[0104] Table 5 Performance data of examples and comparative examples

[0105]

[0106] By comparing Examples 1 to 6 and Comparative Examples 1 and 3, it is found that the impact resistance of the base part of the resin material with the toughening agent added is significantly improved, and its maximum stress intensity factor reaches 2.64 MPa·m 1 / 2 , the total fracture work reaches 3000.23J / m 2 .

[0107] It can be seen from Comparative Example 4 that when the content of the toughening agent exceeds the standard, the impact resistance becomes lower and the flexural strength value also decreases accordingly.

[0108] By comparing Examples 1 to 6 and Comparative Example 2, it can be seen that adding inorganic fillers can enhance the hardness of the tooth part, thereby improving its wear resistance.

[0109] It can be found from Comparative Example 5 that when the content of inorganic filler in the tooth part exceeds the standard, a large amount of white unfused SiO2 exists on the surface of the polymer sample, indicating that it has not been completely polymerized, resulting in failure to test the hardness and strength data values.

[0110] By comparing Example 4 with Comparative Examples 6 to 7, when the denture part and the base part are used in the same monomer, the bonding strength between the two can reach a maximum of 27.98 MPa, while when the denture part and the base part are used in an inconsistent manner, the bonding strength decreases significantly, with a minimum of only 10.11 MPa.

[0111] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A resin material, characterized in that: It consists of an upper layer and a lower layer; the hardness of the upper layer is 30 to 90 HV1; the maximum stress intensity factor of the lower layer is ≥1.9 MPa·m 1 / 2 , total fracture work ≥900J / m 2 ; The bonding strength between the upper layer and the lower layer is ≥15MPa.

2. The resin material according to claim 1, characterized in that The color of the upper layer is tooth color; the color of the lower layer is gum color.

3. The resin material according to claim 1 or 2, characterized in that: The raw materials for preparing the upper layer include, by weight percentage, 30-85% of a first organic resin, 0.1-3% of a first initiator, 14.8-69.8% of an inorganic filler, and 0.01-1% of a first colorant; The raw materials for preparing the lower layer include, by weight percentage: 80-97% of a second organic resin, 0.1-3% of a second initiator, 0.01-19.8% of a core-shell toughening agent, and 0.01-1% of a second colorant; The first organic resin and the second organic resin are of the same type; The core-shell toughening agent has a two-phase structure of a rubber phase and a plastic phase.

4. The resin material according to claim 3, characterized in that The core-shell toughening agent includes methyl methacrylate-butadiene-styrene copolymer.

5. The resin material according to claim 3, characterized in that The first organic resin and the second organic resin include polymers and / or monomers; the polymer includes one or more of polymethacrylate, bisphenol A dimethacrylate, urethane dimethacrylate, polycyclohexyl methacrylate, polyvinyl chloride, polystyrene, polyoxymethylene, polyacetaldehyde and polyurethane; The monomer includes one or more of methacrylate, 2-phenoxyethyl methacrylate, ethylene glycol dimethacrylate, 1,6-hexanediol diacrylate, and dimethacrylate urethane.

6. The resin material according to claim 3, characterized in that The inorganic filler includes one or more of glass, glass ceramics, calcium salts, metal oxides, aluminum silicate, silicon carbide, strontium fluoride, kaolin, clay, mica, aluminum sulfate, barium sulfate, calcium hydroxide, strontium hydroxide, zeolite, silicon dioxide, hydroxyapatite and ytterbium trifluoride.

7. The resin material according to claim 6, characterized in that The glass includes one or more of fluorine glass, borosilicate glass, soda glass, barium glass, glass containing strontium or zirconium, barium aluminosilicate glass and fluoroaluminosilicate glass; The metal oxide includes one or more of aluminum oxide, zirconium oxide, barium oxide and zinc oxide; The calcium salt includes one or more of calcium phosphate, calcium fluoride, calcium carbonate and calcium sulfate.

8. The resin material according to claim 3, characterized in that The first colorant includes one or more of vanadium yellow, cerium praseodymium yellow, lemon yellow, iron oxide yellow, chrome yellow, sunset red, iron oxide red, erbium oxide, chromium oxide, iron oxide brown, iron oxide black, carbon black, titanium dioxide and organic pigments.

9. The resin material according to claim 3, characterized in that The second colorant includes one or more of vanadium yellow, cerium praseodymium yellow, lemon yellow, iron oxide yellow, chrome yellow, sunset red, iron oxide red, erbium oxide, chromium oxide, iron oxide brown, iron oxide black, carbon black, titanium dioxide, organic pigment red and imitation bloodshot.

10. The method for preparing the resin material according to any one of claims 1 to 9, comprising the following steps: Mix the raw materials in the upper layer to obtain an upper layer material; Mixing the raw materials of the lower layer to obtain the lower layer material; The upper layer material and the lower layer material are stacked and then hot pressed to obtain the resin material.

11. The preparation method according to claim 10, characterized in that: The hot pressing time is ≥15min, the temperature is ≥100°C, and the pressure is ≤25Mpa.

12. Use of the resin material according to any one of claims 1 to 9 or the resin material prepared by the preparation method according to any one of claims 10 to 11 in preparing dentures.